Novel, thermostable family-13-like glycoside hydrolase from Methanococcus jannaschii - Kim, J W; Terc, H A; Flowers, L O; Whiteley, M; Peeples, T L (Folia microbiologica, 2001)
A novel glycoside hydrolase from the hyperthermophilic archaeon Methanococcus jannaschii has been cloned into Escherichia coli. Extremely thermoactive and thermostable amylolytic activity was confirmed in partially purified enzyme solution. This enzyme exhibited a temperature optimum of 100 degrees C and a pH optimum pH 5.0-8.0. Hydrolysis of large 1,6-alpha- and 1,4-alpha-linked polysaccharides yielded glucose polymers of 1-7 units. Incubation with amylose displayed the highest activity. The catalyst was activated and stabilized by Ca2+ and exhibited extreme thermostability at 100 degrees C with a half-life of 78 h.
Keywords: glykosidhydrolasy; Polysaccharides; Methanococcus; molekulová hmotnost; Escherichia coli; Glucans; sekvenční seřazení; Calcium; Hydrogen-Ion Concentration; Cloning, Molecular; Molecular Sequence Data; vápník; Glycoside Hydrolases; Temperature; sekvence aminokyselin; Enzyme Stability; molekulární sekvence - údaje; glukany; koncentrace vodíkových iontů; klonování DNA; stabilita enzymů; Molecular Weight; Sequence Alignment; polysacharidy; teplota; Amino Acid Sequence